1996
DOI: 10.1021/bp950079p
|View full text |Cite
|
Sign up to set email alerts
|

Practical Considerations in Operation and Scale-up of Spin-Filter Based Bioreactors for Monoclonal Antibody Production

Abstract: Minimum spin-filter fouling and optimum cell retention at high specific perfusion rates are important for efficient operation of a spin-filter based continuous perfusion bioreactor. We examined the effect of operation conditions and spin-filter configuration on the performance of continuous perfusion bioreactors using a perfusion recycle scheme. This study showed that single cell suspensions foul a spin-filter screen, partially but irreversibly, in the early stages of the bioreactor run. A high perfusion rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 4 publications
3
60
0
1
Order By: Relevance
“…Favre and Thaler (1992) proposed that high rotation rates providing fluid removal forces (calculated as the shear stress at the mesh surface times the projected cell surface area) in the order of 10 -11 N would be enough to prevent colonization of the mesh surface by cells. However, Deo et al (1996) have shown that cells growing in suspension, like NS0 cells, actually clog SFs even at fairly large rotation speeds. Yabannavar et al (1992) and later Vallez-Chetreanu (2006) proposed the hydrodynamic lift to be crucial regarding the probability of a cell to hit and eventually clog the filter mesh.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Favre and Thaler (1992) proposed that high rotation rates providing fluid removal forces (calculated as the shear stress at the mesh surface times the projected cell surface area) in the order of 10 -11 N would be enough to prevent colonization of the mesh surface by cells. However, Deo et al (1996) have shown that cells growing in suspension, like NS0 cells, actually clog SFs even at fairly large rotation speeds. Yabannavar et al (1992) and later Vallez-Chetreanu (2006) proposed the hydrodynamic lift to be crucial regarding the probability of a cell to hit and eventually clog the filter mesh.…”
Section: Introductionmentioning
confidence: 99%
“…So, in spite of the net flow through the mesh be equal to the perfusion flow rate, they proposed the existence of a higher flow due to recirculation through the SF mesh, which was named exchange flow (Yabannavar et al 1992). Deo et al (1996) made an extensive experimental work and proposed that the ratio of the squared tangential velocity to cell concentration was proportional to the perfusion flux capacity of the spin-filter, which defined as the maximum perfusion flux (perfusion flow rate per mesh area) operable without occurrence of fouling. Thus, higher perfusion flows per mesh area would be feasible for higher rotation rates, evidencing the action of the centrifugal force in avoiding clogging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mode of operation has been used for the production of monoclonal antibodies (Banik and Heath, 1995;Tang et al, 2007; and recombinant proteins (AlRubeai et al, 1999;Avgerinos et al, 1990). An example of a 500 L industrial perfusion system for monoclonal antibody production by hyridoma is described by (Deo et al, 1996) where the operation continued for 15 to 35 days to achieve commercial production of antibodies with a cell density of >10 x 10 6 cell/mL. Their results have shown that the volumetric productivity of the perfusion process was approximately 10 times that of batch or fed-batch cultures.…”
Section: Perfusion Culturementioning
confidence: 99%
“…Cell-retention systems available for perfusion systems at relatively large-scale (100-1,000 L/d) are spinfilters (Deo et al, 1996;Yabannavar et al, 1994), hollow fibers/alternating tangential-flow filters (Voisard et al, 2003), centrifuges (Johnson et al, 1996;Takamatsu et al, 1996), settlers (Arai et al, 1993), and acoustic cell separators (Gorenflo et al, 2002). Acoustic separators have no physical barrier and no moving mechanical parts and are, therefore, less prone to fouling and mechanical failure.…”
Section: Introductionmentioning
confidence: 99%